Bardet Biedl syndrome - report of a very rare case - Asha Shirahatti; Daksha Dixit; Harshavardhan Pati (Wolters Kluwer Medknow Publications, 2016)
Bardet Biedl Syndrome is a autosomal recessive condition with a wide spectrum of clinical features. The principal manifestations of the syndrome are Post axial Polydactyly, Retinitis Pigmentosa, truncal obesity, hypogonadism & renal dysfunction. The authors report a case of Bardet Biedl Syndrome in a young girl diagnosed on the basis of post axial Polydactyly, retinitis pigmentosa and other systemic features. Postaxial Polydactyly is one of the earliest and most common manifestation of Bardet Biedl syndrome, followed by truncal obesity and retinitis pigmentosa. Renal failure is the major cause of morbidity and mortality. The importance of Polydactyly lies in the fact that, such finding can be helpful in antenatal diagnosis to see its inheritance, counseling of such families and at times may be treated by surgical correction.